Age Discrimination in the Allocation of Research Funds: The Dutch Model - Wolfgang Stroebe (Center for Research in Economics, Management and the Arts (CREMA), 2009)
The major funding source for fundamental scientific research in the Netherlands (NWO), reserves more than half of their research budget for grants for young researchers. Researchers, who received their doctorate more than 15 years ago, cannot apply. Apparently NWO believes in a negative correlation between age and scientific creativity or productivity. This article reviews research on this relationship and concludes that there is no evidence to support the myth that science is a young person's game. By allocating a major part of their budget to early career award and by under-funding research or individuals in the second half of their careers, NWO may have lowered the level of innovative research in the Netherlands.
Keywords: 330